Unlimited growth of particle fluctuations in many-body localized phases - Kiefer-Emmanouilidis, Maximilian; Unanyan, Razmik; Fleischhauer, Michael; Sirker, Jesko (Annals of Physics, 2021)
We study quench dynamics in a t-V chain of spinless fermions (equivalent to the spin-1/2 Heisenberg chain) with strong potential disorder. For this prototypical model of many-body localization we have recently argued that – contrary to the established picture – particles do not become fully localized. Here we summarize and expand on our previous results for various entanglement measures such as the number and the Hartley number entropy. We investigate, in particular, possible alternative interpretations of our numerical data. We find that none of these alternative interpretations appear to hold and, in the process, discover further strong evidence for the absence of localization. Furthermore, we obtain more insights into the entanglement dynamics and the particle fluctuations by comparing with non-interacting systems where we derive several strict bounds. We find that renormalized versions of these bounds also hold in the interacting case where they provide support for numerically discovered scaling relations between number and entanglement entropies.
CRIS-Team Scopus Importer:2023-03-27
Keywords: Anderson localization; Disordered systems; Entanglement measures; Many-body localization